2016
DOI: 10.15171/joddd.2016.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two prophylaxis methods on marginal gap of Cl Vresin-modified glass-ionomer restorations

Abstract: Background. This study evaluated the effect of two prophylaxis techniques on the marginal gap of CI V resin-modified glass-ionomer restorations.Methods. Standard Cl V cavities were prepared on the buccal surfaces of 48 sound bovine mandibular incisors in this in vitro study. After restoration of the cavities with GC Fuji II LC resin-modified glass-ionomer, the samples were randomly assigned to 3 groups of 16. In group 1, the prophylactic procedures were carried out with rubber cup and pumice powder and in grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…This seepage can cause recurrent caries, pulpal injury, tooth discoloration, hypersensitivity of restored teeth, and accelerated deterioration of the restorative material. 11 To ensure the clinical relevance of marginal adaptation and microleakage, materials should be used that are appropriate to clinical dentistry. Therefore, this study compared three widely used GI-based materials, one of them recently released to dental market named bioactive ionic resin (ACTIVA), which are the best choices for restoring class V. 12 Every effort was made to standardize the methodology, and all steps were conducted by a single operator, and marginal adaptation was evaluated between different specimens using SEM.…”
Section: Gicmentioning
confidence: 99%
“…This seepage can cause recurrent caries, pulpal injury, tooth discoloration, hypersensitivity of restored teeth, and accelerated deterioration of the restorative material. 11 To ensure the clinical relevance of marginal adaptation and microleakage, materials should be used that are appropriate to clinical dentistry. Therefore, this study compared three widely used GI-based materials, one of them recently released to dental market named bioactive ionic resin (ACTIVA), which are the best choices for restoring class V. 12 Every effort was made to standardize the methodology, and all steps were conducted by a single operator, and marginal adaptation was evaluated between different specimens using SEM.…”
Section: Gicmentioning
confidence: 99%
“…This system releases air jet, water and sodium bicarbonate particles that have the size by 250µm, and they may cause loss of resin surface smoothness, therefore they favor the staining and degradation of restorations 10,12 . On the other hand, studies have reported that the abrasiveness from air-polishing can be used as strategy to reduce dental and material surface staining 11,12 , due to the ability of SBAP to remove waste substances containing dyes from food, drinks and cigarette smoke 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Gingival margin gaps were measured using a stereomicroscope (SMZ 1500; Nikon, Tokyo, Japan) at ×40 magnification. 24,29 A digital camera was used to photograph the selected areas with the use of a DS-L2 control unit (Nikon, Tokyo, Japan) so that the gaps could be measured. 24,29 The gap widths were measured with the built-in software in µm by determining two points on each side of the gap (one on the restoration side and one on the root side) and measuring the distance between these two points.…”
Section: Methodsmentioning
confidence: 99%
“…The teeth were cleaned with a rubber cup and pumice and stored in 0.5% chloramine T trihydrate solution for one week and then stored in deionized water in a refrigerator at a temperature of 4ºC. 24 Twenty-four hours before the experimental procedures, the teeth were immersed in deionized water at a temperature of 23±2ºC. 24 To prepare the samples, standard Class V cavities (2 mm in depth, 2 mm in mesiodistal width and 3 mm in the occlusogingival width) were prepared on the buccal surfaces with butt joint margins; the occlusal and gingival margins of the cavities were both placed 1.5 mm occlusal to and gingival to the CEJ, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation